2021
DOI: 10.1101/2021.02.17.431649
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Cell-type specific arousal-dependent modulation of thalamic activity in the lateral geniculate nucleus

Abstract: State dependent thalamocortical activity is important for sensory coding, oscillations and cognition. The lateral geniculate nucleus (LGN) relays visual information to the cortex, but the state dependent spontaneous and visually evoked activity of LGN neurons in awake behaving animals remains controversial. Using a combination of pupillometry, extracellular and intracellular recordings from identified LGN neurons we show that thalamocortical neurons and interneurons are distinctly correlated to arousal forming… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 33 publications
0
9
0
Order By: Relevance
“…On the other hand, related work from our lab has shown that during locomotion the reduction in thalamic bursting and overall increase in firing rates still occurs even when CT feedback is optogenetically suppressed (Spacek et al, 2020). Together, these findings indicate that arousal-related modulations of thalamic activity involve both cortex-dependent and independent mechanisms (Molnár et al, 2021).…”
Section: Discussionmentioning
confidence: 70%
See 2 more Smart Citations
“…On the other hand, related work from our lab has shown that during locomotion the reduction in thalamic bursting and overall increase in firing rates still occurs even when CT feedback is optogenetically suppressed (Spacek et al, 2020). Together, these findings indicate that arousal-related modulations of thalamic activity involve both cortex-dependent and independent mechanisms (Molnár et al, 2021).…”
Section: Discussionmentioning
confidence: 70%
“…While raw pupil size has been successfully employed as a marker for internal arousal processes in sensory circuits (Augustinaite & Kuhn, 2020;Liang et al, 2020;Lin et al, 2019;McGinley et al, 2015a;Molnár et al, 2021;Petty et al, 2021;Schröder et al, 2020;Schwartz et al, 2020), other studies, including ours, have instead considered the pupil size signal as a continuous oscillatory process and focused on its dynamics (Reimer et al, 2014(Reimer et al, , 2016. We further extended this perspective by exploiting a decomposition method that respects the non-stationary, multi-scale nature of the pupil size signal (Huang et al, 1998), and found that several timescales were related to dLGN firing modes.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…On the other hand, related work from our lab has shown that during locomotion the reduction in thalamic bursting and overall increase in firing rates still occurs even when CT feedback is optogenetically suppressed 83 . Together, these findings indicate that arousal-related modulations of thalamic activity involve both cortex-dependent and independent mechanisms 45 . Third, pupil-linked modulations have also been observed in retinal input to the dLGN 37 , which might be mediated by pre-synaptic modulation of the retinogeniculate synapse by serotonin 84 (5-HT).…”
Section: Discussionmentioning
confidence: 81%
“…While raw pupil size has been successfully employed as a marker for internal arousal processes in sensory circuits 10,15,18,22,37,39,[44][45][46] , other studies, including ours, have instead considered the pupil size signal as a continuous oscillatory process and focused on its dynamics 9,11,47 . We further extended this perspective by exploiting a decomposition method that respects the non-stationary, multi-scale nature of the pupil size signal 48 , and found that several timescales were related to dLGN firing modes.…”
Section: Discussionmentioning
confidence: 99%